The Consumer-Driven Food Bio-Packaging Supply Chain – Wishful Thinking or the Future? - Aneta PLUTA-ZAREMBA; Barbara OCICKA; Jolanta TUREK (Communications of International Proceedings, 2021)
Enterprises and supply chains operate in an environment where ecological issues are becoming increasingly important. Development of packaging can incorporate sustainability and  may be one of changes resulting in a lower carbon footprint or use of renewable resources. Growing social awareness and changing consumer preferences for sustainable packaging as well as a willingness to purchase more products in environmentally friendly packaging are increasingly significant trends that may reshape the packaging industry. This paper aims to answer the question whether consumers can drive the food bio-packaging supply chains. The article presents the results of two stages of qualitative research: in-depth semi-structured interviews and focus group discussions. Usage of the two different qualitative research methods was justified by the research problem and enabled to collect data to identify and evaluate the significance of the conditions for the development of a new emerging food bio-packaging market. The results revealed that the current state of the bio-packaging market development is strongly influenced by many barriers that limit the possibilities for food bio-packaging supply chains to be driven by consumer needs. This paper investigates the influence of consumer pressure on using bio-packing by manufacturers of finished goods and its implication on bio-packaging production. Depending on the degree and pace of overcoming barriers, exploiting drivers and exploring enablers, the gradual evolutionary transition of food bio-packaging supply chains to customer-driven ones can take place.
Keywords: Consumer-Driven Supply Chain; Sustainability; Bio-Packaging